Learning through Individuation: How Indonesian Young People Seek a Personal Growth and Self-Development at Alternative Schooling - Rosmilawati, Ila (Universitas Negeri Semarang, 2017)
This present study explores students’ voice who are not in formal education, but participate in non-formal education, especially in the Equivalency Education Program context. These learning experiences are investigated to understand how Indonesian young people seek a personal growth and self-development in the Equivalency Education context. Perspective transformation from depth psychology approach is applied as theoretical framework of this study. The depth psychology approach describes student’s transformation/change as a process of individuation. It means that Indonesian young learners who experience learning as transformative through the process of individuation are those who make sense of their learning through their feelings and emotions, through images, and intuition. The findings suggest that different forms of learning outcomes are encountered by students. These categorisations are based on student reflection on their learning as a result of learning through individuation; (i) students’ development of personal commitment; (ii) students’ positive attitude toward schooling, and (iii) students’ feeling of ‘becoming different’. These three forms of learning outcomes are resulted from the ability of students to acknowledge the individuation process of learning in alternative school context.